OPTIMALISASI PEMAHAMAN LANSIA TERHADAP PENTINGNYA AKTIVITAS SOSIAL DI MASYARAKAT - Endang Sri Wahyuni; Retna Febri Arifiati (Tahta Media Grup, 2025)
Background: The elderly are a group that is vulnerable to decreased physical function and social isolation, so they need empowerment efforts to improve their quality of life. However, many elderly people still have the view that social activities are only for young people or those who are still productive. The purpose of this service is to increase the understanding of the elderly about the importance of social activities in the community through participatory education. Methods: The activity was carried out at Posyandu Lansia Dukuh Tempuran, Bolon Village, on May 17, 2025, using the method of counseling, discussion, and showing educational videos based on the persistent life situations curriculum. The subjects were 41 people consisting of elderly people, cadres, and local midwives. Data were collected using pre and post-counseling questionnaires to assess changes in elderly knowledge. Results: There was a significant increase in the level of knowledge of the elderly, with an average pre-score of 4.68 rising to 9.29 post-counseling. Active participation of the elderly during the activity showed a positive response to the material presented. Conclusion: Counseling is effective in increasing the awareness of the elderly about the importance of social activities for mental and physical health. Follow-up by cadres and regional stakeholders is needed so that the program is sustainable and can reach more elderly people.